Nickel (Ni) allergic patients with complications to Ni containing joint replacement show preferential IL-17 type reactivity to Ni - Summer, Burkhard; Korntheuer, Carina; Mazoochian, Farhad; Rau, Christoph; Thomsen, Marc N.; Banke, Ingo; Gollwitzer, Hans; Dietrich, Karin-Almut; Mayer-Wagner, Susanne; Ruzicka, Thomas; Thomas, Peter (Contact dermatitis, 2010)
Background: Some nickel (Ni) allergic patients develop complications following Ni-containing arthroplasty. In the peri-implant tissue of such patients, we had observed lymphocyte dominated inflammation together with IFN-γ and IL-17 expression. Objectives: To determine whether Ni stimulation of peripheral blood mononuclear cells (PBMCs) of such patients would lead to a different cytokine pattern as compared to Ni-allergic patients with symptom-free arthroplasty. Patients and Methods: Based on history and patch testing in 15 Ni-allergic patients (five without implant, five with symptom-free arthroplasty, five with complicated arthroplasty) and five non-allergic individuals, lymphocyte transformation test (LTT) was performed using PBMC. In parallel in vitro cytokine response to Ni was assessed by real-time reverse transcriptase-polymerase chain reaction (RT-PCR). Results: All 15 Ni-allergic individuals showed enhanced LTT reactivity to Ni (mean SI = 8.42 ± 1.8) compared to the non-allergic control group. Predominant IFN-γ expression to Ni was found both in the five allergic patients without arthroplasty and also in the five allergic, symptom-free arthroplasty patients. In contrast, in the five Ni-allergic patients with arthroplasty-linked complications a predominant, significant IL-17 expression to Ni was seen but not in patients with symptom-free arthroplasty. Conclusions: The predominant IL-17 type response to Ni may characterize a subgroup of Ni-allergic patients prone to develop lymphocytic peri-implant hyper-reactivity.